Portfolio selection based on an volatility measure adjusted for irrationality - Steurer, Elmar Richard (Archives of Business Research, 2019)
This paper investigates the combination of the two risk measures irrationality and volatility for portfolio selection as well as irrationality as a standalone risk measure. The study is conducted for a period of 20 years, ranging from 1999-01-04 to 2018-12-31, using daily closing prices from 1.295 stocks. The companies are derived from the indices S&P 500, STOXX 600 and a representative index of the German market out of the indices DAX, MDAX, SDAX and TecDAX. The findings indicate a negative relationship between risk and return in terms of irrationality across the three indices. The effect is particularly evident when comparing the portfolios with the lowest and highest values of irrationality. Further, the analysis provides an indication of how an index can be replicated with fewer expenses and complexity, particularly regarding the fact that the volatility of the synthetic portfolio is equivalent.